2019
DOI: 10.1109/access.2019.2939281
|View full text |Cite
|
Sign up to set email alerts
|

Toward Deep Learning Approaches for Learning Structure Motifs and Classifying Biological Sequences From RNA A-to-I Editing Events

Abstract: RNA editing is a post-transcriptional RNA sequence modification that alters the mature RNA sequence from its template DNA sequences. RNA editing events are critical in various biological and biochemical mechanisms, and can expand the transcriptomic and proteomic diversity from altered gene regulation to mutations. A-to-I RNA editing is now being vastly detected and quantified on a global scale and gained much attention. A deeper understanding of this process with insufficient genomic annotations and prior know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…PLS with novel TTZ feature vector [ 51 ] is applied to lung disease classification and is able to achieve an accuracy of 92.65%, while the LASSO SVM model is applied to cancer datasets and is able to achieve an accuracy of 91.3%, thereby making them useful for various applications. Similar models have been explained, where the authors have discussed the use of repeated incremental pruning to produce error reduction (RIPPER) [ 52 ], CNNs, RNNs [ 53 ], and RIPPER with SVM for multiple applications [ 54 ]. The RIPPER model is capable of achieving an accuracy of 80.8%, CNNs an accuracy of 96%, RNNs an accuracy of 96.2%, and SVM with RIPPER to achieve an accuracy of 99.7%, thereby improving their utility for real-time clinical and on-field deployments.…”
Section: Genome Sequence Processing Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…PLS with novel TTZ feature vector [ 51 ] is applied to lung disease classification and is able to achieve an accuracy of 92.65%, while the LASSO SVM model is applied to cancer datasets and is able to achieve an accuracy of 91.3%, thereby making them useful for various applications. Similar models have been explained, where the authors have discussed the use of repeated incremental pruning to produce error reduction (RIPPER) [ 52 ], CNNs, RNNs [ 53 ], and RIPPER with SVM for multiple applications [ 54 ]. The RIPPER model is capable of achieving an accuracy of 80.8%, CNNs an accuracy of 96%, RNNs an accuracy of 96.2%, and SVM with RIPPER to achieve an accuracy of 99.7%, thereby improving their utility for real-time clinical and on-field deployments.…”
Section: Genome Sequence Processing Modelsmentioning
confidence: 99%
“…( 5 ) is presented, wherein the accuracy of different genome models for heart and brain sequence data analysis is visualized. It is observed that RIPPER SVM [ 54 ], SHoT [ 27 ], RNN [ 53 ], and CNN [ 53 ] outperform other models in terms of accuracy, and thus must be used for heart and brain dataset genome sequence analysis.…”
Section: Empirical Model Analysismentioning
confidence: 99%
See 1 more Smart Citation